QUANTIFYING THE SURFACE ROUGHNESS EVALUATION OF RAILWAY BALLAST GRAIN UNDER ROTATING DRUM ABRASION - Opu Chandra Debanath; Takashi Matsushima; Shuichi Adachi; Masahiro Miwa (GEOMATE Journal, 2024)
Railway ballast is a crucial component of the railway infrastructure, with the geometric shape and surface morphology of ballast grains playing an essential role in the overall strength of the ballasted track. This study investigates the evolution of surface roughness for two types of railway ballast, Andesite and Sandstone, at various stages of abrasion using a rotating drum test. The surface texture changes are analyzed by comparing amplitude roughness parameters and power spectral density distributions. Additionally, the overall grain shape change is tracked by grain shape parameters: ellipsoid volume ratio and rotation resistance angle. A 3D scanning workflow is developed using the focus stacking method; the accuracy is verified by standard surface S-22. Experimental findings reveal that laboratory-abraded ballast grains exhibit significantly lower roughness than fresh ballast grains, following a power law decay with abrasion cycles. Notably, roughness does not differ substantially between the Andesite and Sandstone ballast. The observed surface roughness evolution is attributed to the progressive removal of surface peaks through continuous attrition at the interfaces between grains and the drum wall. Furthermore, the study reveals that the abrasion process primarily involves the removal of surface texture, followed by subsequent changes in angularity and overall grain shape.